EFEKTIFITAS PELAKSANAAN BUSINESS DEVELOPMENT SERVICE (BDS) OLEH DIREKTORAT JENDERAL PAJAK - Rosyadi, Imron; Hadiyati, Ernani; Astuti, Rini (Arthavidya Jurnal Ilmiah Ekonomi, 2020)
Abstract : Since 2016, Indonesian Directorate General of Taxes (DGT) providedBDS’s program aimed to encourage the development of SMEs business andimprove their tax compliance. This study employed the case study method asthe framework, where participants were given the opportunity to provide as muchinformation as possible about their experiences in implementing the programs.The information then collected and sorted according to the sub-related categories.The results of the study indicate that BDS implemented by DGT generallyprovides positive results. There were several factors that determined the successof BDS implementation, namely employee’s participation, seminar material, andcooperation with the third parties. While the factors that were the constraint onesin the BDS implementation was the limited time, cost, and the human resource ofthe DGT itself. SME’s gets positif gain from the program. In addition, the BDSprogram has been proven to reduce the negative perception of SME actors ontaxes.Keywords: Business Development Service, SME , Tax Compliance, Tax Policy,